ROLE OF NEUROSPECIFIC PROTEINS IN THE DEVELOPMENT OF COGNITIVE DYSFUNCTION IN PATIENTS WITH TYPE 1 DIABETES - M. V. Novosyolova; Yu. G. Samoilova; N. G. Zhukova; A. V. Latypova (Бюллетень сибирской медицины)
Type 1 (type 1 DM) diabetes mellitus is one of the common chronic metabolic diseases, which currently is a significant problem due to disability at a young age and reduce life expectancy. Despite the fact that type 1 diabetes accounts for only 10% of all patients with diabetes, it occurs particularly hard, with a tendency to progression. One of the targets of type 1 diabetes is the central nervous system with the further formation of cognitive dysfunction in young age leads to diminished quality of life. Cognitive deficits may be the result not only of structural lesions of the brain, but it may be due to the development of metabolic disorders. In the case of timely diagnosis and treatment of cognitive impairment associated with metabolic changes that can partially or completely regress. The aim of this study was to identify biomarkers of the brain damage in young patients with type 1 diabetes. The study involved 58 patients with  type  1  diabetes,  the  control  group  comprised  29  healthy  controls.  The  complex  included a neuropsychological examination which was used for testing the Montreal scale (MoCA test) rapid screening of cognitive impairment, assessment of quality of life using a common questionnaire Medical Outcomes Study Short Form (MOS SF-36) and the specific audit – dependent quality of life (ADDQoL). To evaluateearly markersin the developmentof cognitive dysfunctionwere identifiedneurospecific proteins – S100 protein and glial fibrillary acidic protein (GFAP), myelin basic protein (MBP). Found an increased level of neurospecific protein that was correlated with parameters of carbohydrate metabolism, poor quality of life and severe cognitive deficiency (MoCA test lower than 26 points).